Analysis of Development Program Strategy, In-Class Training, and Employee Family Day on Employee Turnover at PT. Astra Motor - Benediktus Suryawan Salim (Publikasi Indonesia, 2025)
High employee turnover rates pose a serious challenge for companies in maintaining organizational stability and productivity. This study aims to analyze the influence of employee development strategies through development programs, in-class training, and employee family day programs on employee turnover rates at PT. Astra Motor. The research method used a quantitative approach by distributing questionnaires to several respondents who are permanent employees of PT. Astra Motor. The data obtained were analyzed using multiple linear regression to determine the relationship and influence of each variable. The results show that all three strategies have a significant influence on reducing turnover, both partially and simultaneously. Development programs contribute to building employee loyalty through increased competency and clear career paths. In-class training plays a role in increasing self-confidence and technical skills, while employee family day strengthens the emotional bond between employees, their families, and the company. This study recommends that management continue to strengthen these strategies as part of a holistic approach to human resource management.